To sleep or not to sleep: An Italian Control-IQ-uestion - Bassi, Marta; Strati, Marina Francesca; Andreottola, Valentina; Calevo, Maria Grazia; d’Annunzio, Giuseppe; Maghnie, Mohamad; Minuto, Nicola (Frontiers in Endocrinology, 2022)
Objective: Tandem Control-IQ is an Advanced Hybrid Closed Loop (AHCL) system with a Sleep Activity Mode to intensify glycemic control overnight. The aim of the study is to evaluate the effectiveness of using Sleep Mode or not among Tandem Control-IQ users. Research design and methods: We performed retrospective Tandem Control-IQ data download for the patients followed at IRCCS G.Gaslini Pediatric Diabetes Centre. We divided the patients into Group 1 (Sleep Mode users) and Group 2 (non-users) and compared their overall glycemic data and in particular during night-time. Results: Group 1 does not show a better nocturnal glycemic control as expected, when compared to Group 2. Group 2 shows a higher night-time TIR% (69.50 versus 66.25, p = 0.20). Only the patients who do not use Sleep Mode and with sensor and automatic mode use ≥ 90% reached TIR > 70% during night-time, as well as lower nocturnal TAR% (18.80 versus 21.78, p = 0.05). Conclusions: This is the first study that evaluates the real-life effectiveness of the use of Sleep Mode in young patients with T1D. Control-IQ Sleep Activity Mode may not be as effective in Italian patients as in American patients due to the different habits.